On the night train to the Big Adios : Colloquial language in L.A. Confidential (1997) - Lindqvist, Suvi (fi=Turun yliopisto|en=University of Turku|, 2018)
The purpose of this study is to examine the Finnish subtitles of the American neo-noir L.A. Confidential (1997), evaluate them from a linguistic perspective, and determine whether the heavily colloquial language of the film has been retained in the translation. A secondary interest is characterization, or how the variety in dialogue in terms of different characters has been noted in the subtitles. The study was carried out by collecting all the colloquial expressions in the film, organizing them according to the translation strategies used, and then analysing and discussing them from a linguistic and stylistic point of view. The analysis of the colloquial expressions showed that the most commonly used translation strategies were modulation and slang equivalence, which in turn indicated that the translation was successful in terms of retaining as much colloquial language as possible. Although many characters lost their colorful language in translation, paralanguage (e.g. intonation) and other non-linguistic aspects are helpful when the viewer makes assumptions about the nature of different characters, and therefore what is lost in translation can be made up with the relationship of image and text, which is typical for subtitling. In conclusion, because language in films is merely an imitation of real face-to-face spoken language, this poses challenges for translators, but within the parameters of how much colloquial language can be retained in a written form of speech, this particular translation was successful.